(3MGTjI GdMdHj Ydi TQM GdefgL efgL GdWdGHs - (3GdMdHj, CHh GdaQL, GHf HQgGf GdOjf, fhQ GdOjf, Ydj Hf EHQGgje Hf CMeO, J (B1044 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; bhdg eMjj GdOjf fbd Yf GdEeGe Gdfhhj Cfg bGd (B: (3djS aj Md ef bGd Yfj eMjj GdOjf , hgPG ef hQYg hJhGVYg adG jbGd ebJVi Pdc MQeI EWdGb gPG GddaX Ydjgs
(3BNQgG (B:s
(3bhdg dG jDOj HPdc HCSG HGdjGA GdJMJjI bhdg (B: (3GSJOdGdG hGLJgGOG ef hMed UjZI dG jHYf Ydi GdcQGgI NdGa GdXGgQ bhdg ceG CaJi Hg GdbaGd eYJeO gPGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 251s
(3eYLe GdeDdajf (B2 / 386s
(3gOjI GdYGQajf (B1 / 755s
(3NdGUI GdCKQ (B3 / 122s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs